Analisis pengaruh pendidikan dan pelatihan teknis serta motivasi terhadap kinerja alumni balai pendidikan dan pelatihan industri regional i di medan - James Ronald Tambunan (Jurnal Widya, 2020)
Balai Diklat Industri Regional – I Medan us one of technical executive unitaries in education and training sector is responsible for center for Industrial Education and Training of the Ministry of Industry. Since Regulation number 22 year 1999 for local autonomy is legalized and then has been changed to regulation number 32 year 2003, there are many changes in the structure of organization including reposition and substitution of functionaries and officials in industrial service institution. Due to the reposition, there are many officials still do not have enough technical substantive knowledge about industry sector as their aquip to do their dutter. In order to repair this condition, technical training needs to be done. It aims to synchronize perception between the older and the newer ones. The purpose of this research is to look for and analyze the effect of Technical Training and motivation of alumnae’s work in Balai Diklat Industri Regional I Medan. Hypothesis of the research is Technical Training and motivation affect alumnae’s work in Balai Diklat Industri Regional I Medan. Method use in taking the samples is by using Slovin Formulation in which from 179 populations about 124 samples are taken. Hypothesis is tested by using compound linear regressive analysis. It is held by doing simultaneous test (f test) and partial Test (t test). Both of tests have purpose to know the effect of independent variable to dependent variable on relieance level 95% or ? = 0,005. The result of analysis shows that Technical Training and motivation have simultaneous and significant effect to work motivation of alumnae in Balai Diklat Industri Regional I Medan. The significant level is 0.000. Determinant Coefficient (R2) of independent variable to dependent variable is about 59,3 % and the rest (40,7 %) is affected by another variable that is not used in this research. The result of t test (partial test) shows every independent variable used has significant effect to its dependent variable. Technical Training variable has real effect to the work with significant effect to the work 0.01 with significant level 0,000 smaller than 0,005 (5%).